Teaching the Concepts of Surah al-Fil by the Exploratory Education Method of Storytelling - Bibi Zeinab Hosseini; Abolfazl Alishahi Ghale Jooghi (پژوهش در آموزش معارف و تربیت اسلامی)
One of the efficient and new educational methods is the explorative education method. The Noble Qur’an has paid attention to this method in its way of expression and has taught the concepts and contents to the learners or students by using words in various frameworks and types of explorative education. One of these methods is storytelling and, in this regard, the purpose of the present research is to review educational methods of teaching the concepts in Surah al-Fil by the exploratory method of storytelling. In Surah al-Fil, the important and historical account of the attack of Abraheh to Mecca has been narrated through a short story in which two hapax legomena of “Ashāb al-Fil” and ‘Abābil” have been used. This usage raises a question a question for students that why God has used these terms for the first time. Searching and attempt to explore the reason of this application leads students to the important necessity of adopting a smart strategy in facing with problems. It is a significant achievement that perhaps has not been dealt with in the previous exegeses; however, the explorative education method by raising purposive questions, can help the students to reach that.